Outcome of anemia among high-risk pregnant women in a primary health centre - Kottu, Madhusudhana Rao; Kothapalle, Sowmyasudha; Viswanath, Adi Natesh Katta; Gottumukkala, Raviprabhu (International Journal Of Community Medicine And Public Health, 2022)
Background: Anaemia is the most common nutritional deficiency in high-risk pregnancies especially in developing countries like India. Though it is easily treatable and preventable condition it is a major factor in high-risk pregnancies. Primary health care medical officers are the first person in the community to identify and manage anaemia in pregnant women, by improving dietary habits and vitamin supplementation (iron, folic acid and). Aim of the study was to determine the various out comes among anemic pregnant women with other high-risk factors. Objectives of the study was to estimate the prevalence of anaemia in high-risk pregnancy, to assess socio-demographic profile of study subjects and to determine the pregnancy outcome. Methods: A longitudinal follow up study was done by using a convenient sampling method a total of 112 high risk antenatal mothers were selected to do this study. They were followed till their delivery. Results: Overall prevalence of anaemia among high-risk pregnant women was found to be 82%. Among all the high-risk pregnant women 31% were having intermediate, 73% belongs to upper middle class, 57% underwent normal delivery. Only a few 2.5% had MTP, 39% had mild anemia, 23% had moderate anemia, 20% had severe anemia. Conclusions: Awareness regarding the complications of anemia and its prevention must be educated to high risk anenatal mothers.